2020
DOI: 10.1093/mnras/staa1883
|View full text |Cite|
|
Sign up to set email alerts
|

Can magnetized turbulence set the mass scale of stars?

Abstract: Abstract Understanding the evolution of self-gravitating, isothermal, magnetized gas is crucial for star formation, as these physical processes have been postulated to set the initial mass function (IMF). We present a suite of isothermal magnetohydrodynamic (MHD) simulations using the GIZMO code, that follow the formation of individual stars in giant molecular clouds (GMCs), spanning a range of Mach numbers found in observed GMCs ($\mathcal {M} \sim 10-50$). As i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 130 publications
6
38
0
Order By: Relevance
“…The field strength is not as high in our simulation because the field is quenched as a result of the limited resolution for a minimum cell size of 4 AU, and turbulence hampers the pile-up of the magnetic field in our model, similar to the recent results by Guszejnov et al (2020). If we resolved the vicinity of the young star in more detail, we would reach higher densities and higher magnetic field strengths as a consequence of flux-freezing.…”
Section: Distribution Of the B-field Strengthsupporting
confidence: 74%
“…The field strength is not as high in our simulation because the field is quenched as a result of the limited resolution for a minimum cell size of 4 AU, and turbulence hampers the pile-up of the magnetic field in our model, similar to the recent results by Guszejnov et al (2020). If we resolved the vicinity of the young star in more detail, we would reach higher densities and higher magnetic field strengths as a consequence of flux-freezing.…”
Section: Distribution Of the B-field Strengthsupporting
confidence: 74%
“…the mean stellar mass is ∼4 M in the simulations, while ∼0.4 M is observed). This study also found that stellar masses in isothermal magnetohydrodynamics (MHD) also increase with time and are sensitive to initial conditions (ICs; see analysis in section 4.2 of Guszejnov et al 2020), leading to order of magnitude variations in the predicted characteristic scale of the IMF. Observations, however, have found the IMF to be near-universal within the MW, with variations in the IMF peak mass within a factor of <3 (see reviews of Bastian, Covey &Meyer 2010 and, as well as analysis of Dib 2014).…”
mentioning
confidence: 61%
“…Padoan et al 2007;Padoan & Nordlund 2011;Haugbølle, Padoan & Nordlund 2018). While some of these studies claimed to reproduce the observed initial mass function (IMF), our recent study (Guszejnov et al 2020) showed that, for clouds similar to giant molecular clouds (GMCs) in the Milky Way (MW), the mean stellar masses predicted by these magnetized, gravoturbulent models are an order of magnitude higher than observed (i.e. the mean stellar mass is ∼4 M in the simulations, while ∼0.4 M is observed).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Cooling physics for large dynamic range: Our cooling module includes dust-gas thermal coupling, cosmic raygas coupling, and a treatment for optically thick cooling, which is crucial to capture the thermodynamic state of gas at the densities reached in the nuclear disk (n H > 10 7 cm −3 ). The same cooling physics has been used for individual molecular cloud-scale simulations (Grudić et al 2018;Guszejnov et al 2020) reaching 10 −5 pc resolution. 8.…”
Section: Discussionmentioning
confidence: 99%